(3JbQjQGJ GdCUhds - (3eLghds
(3ChdgG (B:s
(3ChdgG(B: (3GdehUdI HCj eYjGQ YHQJ gj eVHhWI djS ajgG YdGbI GdRhLjI hGdedcjI hGdQjGSJjI hGdeQDSjI Edi ZjQ Pdc eeG jJNjd adG jecf GdJYOj efgG EdjgGs
(3BNQgG (B:s
(3BNQgG(B: (3MGd GdfWb hEf Hbj dc UYhHI aj EOQGc gPg GdJTbjbGJ hGdJObjbGJ GdJj HPdJ OhfgG hOhf CeKGdgG LgOj hde jSHbfj aj cKjQ efgG CMO ajeG CYde aGSJYf aj Pdcs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3CUhd Gdabgs